Variance investigation on the microstructural characteristics of vessels among three lignocellulosic biomasses - Ming Yao; Zhaoyang Yu; Yuan Liu; Shanshan Chang; Xianjun Li; Jinbo Hu; Ting Li; Denis Rodrigue; Xiaodong Wang (Scientific Reports, 2024)
Abstract Especially, the processing and utilization of biomass-based material is closely related to the vessel, e.g. the flow of vapour and additive. It is conventional that vessels in most plants can influence on water and nutrients transport between adjacent cells, which could just infer to be important in the wood-based panel industries. In this work, a complete characterization of vessels and pits is presented for three conventional biomasses in wood-based panel: poplar (Populus deltoides) (P), moso bamboo (Phyllostachys edulis) (B), and the fruit shell of oil camellia (Camellia Oleifera) (FS_OC). Every material is analyzed by combining several techniques including: light microscopy, scanning electron microscopy and surveying calculations from resin casting. The results show that among the three biomass materials, B has a significantly larger vessel width (164.8 ± 6.0 μm for B, 2.2 ± 6.2 μm for P, 10.0 ± 0.8 μm for FS_OC) and smaller inclination angle of the perforation plates (6.8° for B, 44.7° for P), which is more conductive to improving moisture transfer between the vessels. The vessel length of P varies widely from 676.8 μm to 1025.2 μm, which is related to its seasonal growth. By resin casting analysis, more differences in the morphology and distribution of pits in the vessel walls were observed between the three species. Such as, For B, there are numerous pits between vessel cells, while very few to none between vessel and parenchyma cells or fiber. In addition to pits, B and FS_OC also have spiral thickening structures on their vessel walls. The pit membrane is an elliptical shape in P, while slit-like shape in FS_OC and a combination of both elliptical and slit-like shape in bamboo. The unique microstructural characteristics of vessels is related to the individual plant growth traits, which is the basis for biomass-based material processing and utilization.